Pengaruh Pemanfaatan Sistem Informasi Akuntansi Keuangan Daerah Dan Pemahaman Akuntansi Terhadap Kualitas Laporan Keuangan Dengan Internal Audit Sebagai Variabel Intervening - Almira Alifina Islamay; Sri Trisnaningsih (Journal of Economic, Bussines and Accounting (COSTING), 2022)
This study aims to determine and examine the impact of the application of regional financial accounting information systems and accounting understanding on the quality of financial reports with internal audit as an intervention variable at the Regional Financial and Asset Management Agency of the City of Surabaya. This research utilized quantitative methods. The study sample was taken from the Regional Financial and Asset Management Agency of the City of Surabaya with the total sampling method. The participants in this research were 35 participants consisting of staff in the accounting and treasury fields. The data analysis technique used is path analysis, hypothesis testing, inner model analysis and outer model analysis, with the help of SmartPLS 3.0. The results indicates that the use of regional accounting information systems had no meaningful impact on the financial statements quality. Accounting understanding has a positive and significant effect on the Quality of Financial Statements. Utilization of Regional Financial Accounting Information System has no meaningful impact on Internal Audit. Accounting understanding has a positive and meaningful impact on Internal Audit. Internal Audit has no meaningful impact ect on the Quality of Financial Statements. Utilization of the Regional Financial Accounting Information System has no meaningful impact on the Quality of Financial Reports through Internal Audit as an intervention variable. Accounting understanding has no meaningful impact on the Quality of Financial Statements through Internal Audit as an intervention variable. Keywords : Regional Financial Accounting Information System, Accounting Understanding, Quality of Financial Reports, Internal Audit